Effect of weld seam orientation and welding process on fatigue fracture behaviors of HSLA steel weld joints. (August 2020) - Kim, Younghune; Hwang, Woonbong
Graphical abstract: Highlights: Welds are created with laser beam or plasma arc techniques, but often constitute the weak point in steel structural entities. Weld performance often depends on the orientation of the weld, and transverse and diagonal welds are commonly used. With high-strength low-alloy steels, transverse welds exhibit higher fatigue life than diagonal welds. With high-strength low-alloy steels, laser welded seams exhibit higher fatigue lives than plasma-arc welded seams. Abstract: Welded steel structures can be exposed to high dynamic forces and failure typically occurring at the weakest zone within a few (less than 10 2 ) cycles. In order to investigate low-cycle fatigue fracture in weld joints of high-strength low-alloy (HSLA) steels, we have studied the fatigue properties in different weld seam orientations and welding processes. The fatigue performance showed that with transverse welding, fatigue lives at high strains (2%) were approximately seven times higher than with diagonal welding, and, for laser welded seams, fatigue lives were approximately two times higher than those for the plasma arc welded seams.